Preliminary establishment of chronic Parkinson's disease in rhesus monkey model induced by injection of MPTP - Shi Liangqin; Luo Qihui; Zeng Wen; Gong Li; Cheng Anchun; Bi Fengjun; Zeng Licai; Chen Shanshan; Chen Zhengli (浙江大学学报. 农业与生命科学版, 2014)
Parkinson's disease (PD) is a common and age-related progressive neurodegenerative disorder, and its pathogenesis is not yet entirely clear. The present study is to establish a model easy to control and better simulate the clinical symptoms, processes and pathological changes of PD patients, expecting to provide a foundation and platform service for pathogenesis and treatment research of Parkinson's disease.Twelve healthy aging female rhesus monkeys, divided into experimental group (nine rhesus monkeys) and control group (three rhesus monkeys) randomly, were respectively daily injected a small dose (0.2 mg/(kg·d)) of 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) and the same dose of saline by intramuscular injection for 45 days repeatedly. The behavioral manifestations of all monkeys were evaluated before and after the injection for 30 min, respectively. After sacrificed, the expression and distribution of tyroxine hydroxylase (TH) and α-synuclein (α-syn) in substantia nigra were studied by immunohistochemical method, and the immunopositive total area and average optical density were used to validate the model.The results of behavioral manifestations indicated that, experimental animals showed three different degrees of clinical manifestations and could be divided into three subgroups (three animals each subgroup) according to the behavioral and clinical manifestations. The first subgroup showed typical behavioral manifestations of Parkinson's disease and one animal was in the moribund period. The activity, posture and bradypraxia of the third subgroup were slightly abnormal, and behavioral manifestations of the second subgroup were between the first and the third subgroup. However the control group did not show any abnormality. The immunopositive productions of TH were mainly distributed at the cytoplasm and neurites. Compared with the control group, the positive cytoplasm and neurites of the first subgroup were severely reduced, even no positive production was observed in partial substantia nigra pars compacta; the neuron structure of the third subgroup was mild blurred, and neurites were slightly shorter and fewer; the positive productions and structure of the second subgroup were between the first and the third subgroup. Also compared with the control group, the positive total area of each group decreased by 71.90%, 61.90% and 45.74%, showing statistical significance (P<0.01). The immunopositive productions of α-syn mainly distributed at neuritis, and also distributed at the intercellular substance, and Lewy bodies were detected at the substantia nigra pars compacta of the moribund animal. Compared with the control group, positive total area of each group increased by 170.29%, 137.82% and 47.88%, showing statistical significance (P<0.01).The above results suggest that the aging rhesus PD animal model can be established via small doses and repeated intramuscular injection of MPTP, and the PD model can better simulate the clinical behavioral manifestations, disease processes and pathological changes of PD patients, so the model is more reliable for etiology, pathogenesis, drug therapy and gene therapy of Parkinson's disease.